Liquid Crystalline Behavior of Dimers Containing 1, 3, 4-Oxadiazole Unit - Saeed, Zahraa Sabah (Al-Nahrain Journal of Science, 2018)
The synthesis and liquid crystalline properties of new series of 1,3,4-oxadiazole derivative are reported. (2-[(4-methoxy benzylidine amino)-5-(4-hydroxy-phenyl)]-1,3,4-oxadiazole) (II) was synthesized by condensation of (2-amino-5-(4-hydroxy phenyl)-1,3,4-oxadiazole) (I) with (anisaldehyde). A dimmer series with structural formula (III) were synthesis by dimmerization of compound (II) with appropriate (malonic acid, succinic acid, glutaric acid, adipic acid, and palmic acid). The liquid crystalline properties of dimmer series (III) was examined by hot-stage polarizing microscope and showed the presence of nematic mesophases.